Curriculum and Educational Identity: Assessing the Role of Merdeka Curriculum in Student Character and Competency Building - Hikmah, Nuril; Wiharja, Oqi Sintia (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2025)
The implementation of the Merdeka Curriculum in Indonesia is a fresh innovation in the educational system, from the teaching methods to the learning results. The goal of the autonomous curriculum is to develop kids' character by giving them opportunity to study informally, quietly, joyfully, and while paying attention to their inherent abilities.This research uses a qualitative case study approach from a literature study to examine the use of an integrated curriculum on students related to aspects of learning experiences, competencies, and learning interactions. The Merdeka Curriculum gives students the ability to autonomously plan and create learning strategies that suit their needs and environment. The Pancasila students’ profile, which includes faithful, devoted to god almighty, and, noble, globally diverse, mutual cooperation, independent, critical reasoning, and creativity, is used in this project-based curriculum to develop soft skills and character while focusing on key concepts and being implemented flexibly. In order to produce superior human resources and character developed in accordance with existing characteristics with various activities and stages that ultimately result in students with character and collaboration, it is anticipated that this curriculum will strengthen learning outcomes, strengthen character, and collaborate with various parties both nationally and internationally.